2021
DOI: 10.1002/jcc.26492
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatically embedded molecules‐in‐molecules approach and its application to molecular clusters

Abstract: We report the application of our fragment-based quantum chemistry model MIM (Molecules-In-Molecules) with electrostatic embedding. The method is termed "EE-MIM (Electrostatically Embedded Molecules-In-Molecules)" and accounts for the missing electrostatic interactions in the subsystems resulting from fragmentation. Point charges placed at the atomic positions are used to represent the interaction of each subsystem with the rest of the molecule with minimal increase in the computational cost. We have carefully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…With a bird’s-eye view, while accuracy has been a major issue for docking algorithms, speed is the major concern for QM/MM FEP-based approaches. These can be addressed by focusing on critical factors such as incorporation of QM information in docking scoring functions, intelligent implementation of the Zwanzig equation, , development of multilayered fragment-based QM methods, and system-dependent selection of QM sizes in QM/MM models. Nonetheless, with further development in computer power and more accurate methods, CCDD is poised to become a great tool in medicinal chemistry in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…With a bird’s-eye view, while accuracy has been a major issue for docking algorithms, speed is the major concern for QM/MM FEP-based approaches. These can be addressed by focusing on critical factors such as incorporation of QM information in docking scoring functions, intelligent implementation of the Zwanzig equation, , development of multilayered fragment-based QM methods, and system-dependent selection of QM sizes in QM/MM models. Nonetheless, with further development in computer power and more accurate methods, CCDD is poised to become a great tool in medicinal chemistry in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Variational formulation and implementation of analytic derivatives of the method enable efficient MD simulations . The DSCF (double self-consistent field) form has some similarity with fragmentation methods such as FMO and EE-MIM …”
Section: Introductionmentioning
confidence: 99%
“…20 The DSCF (double self-consistent field) form has some similarity with fragmentation methods such as FMO 21 and EE-MIM. 22 The analogous methods for ONIOM (QM:QM) have not yet been fully developed. Two different methods were proposed by our group to account for the missing interactions separately, viz., ONIOM-CT 23,24 (ONIOM with Charge Transfer corrections) and ONIOM-EE 25−28 (ONIOM with electrostatic embedding) to correct for charge transfer and electrostatic interactions, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…21 However, a recent study found that no definite conclusion can be drawn on the suitability of these two charge types for capturing long-range electrostatic interactions. 24 When compared to the DDEC method, it is well known that the CM5 method can cause smaller charges in metal sulfide MS 2 and metal selenide MSe 2 solids but larger charges in other lattices. 25 Therefore, for various MOFs, pairwise comparisons among Mulliken, CM5 and DDEC charges are warranted.…”
Section: Introductionmentioning
confidence: 99%